Focus - Cheng, Tze Ying (2016)
Leveraging on proxemics and behavioral psychology, this project seeks to augment the dining experience and optimize service efficiency in restaurants. This project subliminally integrates well-established intuitive signaling colors into numerous refined forms. The user experience was re-imagined and encapsulated in an entirely new interface and interaction process. Business processes were isolated and analyzed for better understanding of the impact of tangibles and intangibles on both customer experience and satisfaction.